SUPPLY CHAIN ANALYSIS OF SOYBEAN RAW MATERIALS ON TOFU BUSINESS GROUP AT MEROBOK CENTRAL LOMBOK - Abidin, Zainal (Jurnal Magister Manajemen, 2021)
This research is motivated by the problem of raw material shortages that experienced by Tofu business group at Merobok. The research aims are to find out the mapping and to identifiy supply chain problem of soybean raw materials on Tofu business group at Merobok Central Lombok. Type of this research is descriptive study with qualitative approach. Data collecting technique was used in-depth interview, direct observation, and documentation. Then performed qualitative analysis by using Triangulation procedure. As for the results of this research concluded that Tofu business group apply Few Supplier strategy that is choose three supplier consisting of Ingin Maju farmers (ten persons of farmers), H. Abidi as a merchant, and Mr. Sahlan as a collector at Gemel village. However, Tofu business group more intensive to purchase raw materials from Mr. Sahlan (collector). Tofu business group including of weak buyers of soybean raw materials because unable to dominate supplier and Tofu business group has less purchasing power than other buyers and unable to search other suppliers because they have less available capital